Determinants of Employee Performance - Hendra Siregar, Alex; Isa Indrawan, Muhammad (PT. Multidisciplinary Press Indonesia, 2024)
This research aims to determine the influence of organizational culture on employee performance with work motivation as an intervening variable at the BPJS Employment Kisaran and Kediri branch offices. This research was conducted at BPJS Employment in two branches, namely at the Kisaran Branch Office Jl. Sisingamaraja No. 460, Kisaran, Sendang Sari, Asahan, Asahan Regency, North Sumatra 21211 and at the Kediri Branch Office Jl. Mayor Bismo No.34, Semampir, Kota District, Kediri City, East Java 64121. This type of research is quantitative, the research population is 71 employees and the sample used is also 71 employees and uses a saturated sampling technique. The data collection used was a questionnaire and the data source was primary, the model used was phat analysis of the results of this research as follows: Organizational culture has a positive and significant effect on employee performance with an original sample value of 0.435 and a p value of 0.000 <0.05. Organizational culture has a positive and significant effect on work motivation with an original sample value of 0.771 and a p value of 0.000 <0.05. Work Motivation has a positive and significant effect on Employee Performance with an original sample value of 0.474 and a p value of 0.000 < 0.05. Organizational Culture has an indirect and significant positive effect on Employee Performance through Work Motivation with an original sample value of 0.366 and a p value of 0.000.